Minimum Dietary Diversity for Children aged 6–23 months as a predictor of micronutrient adequacy in Ethiopia: Validation of the proxy indicator - Yonatan Menber; Tefera Belachew; Netsanet Fentahun (PLoS ONE, 2025)
Background The Minimum Dietary Diversity for Children aged 6–23 months (MDD-C) is a proxy indicator of micronutrient adequacy. There is a lack of evidence regarding the performance of this proxy indicator, including in Ethiopia, a country with diverse dietary habits. Therefore, this study aimed to validate the performance of MDD-C to predict micronutrient adequacy against the Mean Adequacy Ratio (MAR) among children aged 6–23 months in the North Mecha District, Northwest Ethiopia. Methods A community-based cross-sectional study was conducted among 457 randomly selected study participants from February 2–18, 2023. A single multiphasic interactive 24-hour dietary recall was used to collect dietary intake data. Spearman’s rank correlation test, Cohen’s kappa statistics, and Receiver Operating Characteristic Curve analysis were conducted. The optimal cutoff point for MDD-C was determined by selecting the points that maximized the Youden index. Statistical significance was determined with a p-value < 0.05 using a 95% confidence interval. Results The MDD-C had a moderate positive correlation (ρ = 0.62, p < 0.001) and a fair predictive ability (AUC = 0.78, 95% CI: 0.74, 0.83, p < 0.001) with the MAR to predict the micronutrient adequacy. The MDD score (≥5 food groups) had a sensitivity of 22.4% and a specificity of 91.4%, denoting slight agreement. The optimal cutoff point for MDD-C was found to be ≥ 3 food groups, with a sensitivity of 85.5% and a specificity of 62.9%. This optimal cutoff adjustment improved the agreement between the MDD-C indicator and micronutrient adequacy to a moderate level. Conclusions The MDD-C had a moderate positive correlation and a fair predictive ability with the MAR to accurately predict micronutrient intake adequacy at the optimal cutoff, despite poor sensitivity and high specificity at the standard cutoff. Countries need to adapt MDD-C cutoffs to local dietary patterns to improve accuracy. WHO and UNICEF should revisit the global application of a uniform cutoff and support the development of context-specific thresholds. This study in Ethiopia underscores the importance of further research to reassess the effectiveness of MDD-C as a proxy indicator for determining micronutrient adequacy across diverse populations and multiple countries.